METHODS OF TEACHING MATHEMATICS IN ACADEMIC LYCEUMS - Yuldasheva Umida Tukhtamurodovna (Journals Park Publishing, 2023)
Traditional academic lyceum classes include, as you know, lessons in learning new material, consolidating knowledge, skills and abilities, checking and accounting for acquired knowledge, skills and abilities, analyzing control papers, generalizing and systematizing what has been learned, repeating a topic or section. Along with these forms of education, non-traditional or non-standard ones have recently been widely used, thanks to which students learn program material faster and better.
Keywords: mathematics, teaching methods, pupil’s talents, curriculum, educational process